Selective synthesis of thioethers in the presence of a transition-metal-free solid Lewis acid - Santoro, Federica; Mariani, Matteo; Zaccheria, Federica; Psaro, Rinaldo; Ravasio, Nicoletta (Beilstein Journal of Organic Chemistry, 2016)
The synthesis of thioethers starting from alcohols and thiols in the presence of amorphous solid acid catalysts is reported. A silica alumina catalyst with a very low content in alumina gave excellent results in terms of both activity and selectivity also under solvent-free conditions. The reaction rate follows the electron density of the carbinol atom in the substrate alcohol and yields up to 99% and can be obtained for a wide range of substrates under mild reaction conditions.
Keywords: no solvent; S-alkylation; solid acids; thioethers; transition-metal-free

An Introduction to Green Chemistry Methods - Luque, R.; Colmenares, J. C. (Future Science Ltd, 2013)

Green Chemistry for Environmental Sustainability - Sharma, S. K.; Mudhoo, A. (CRC Press, 2010)

(untitled) - Arancon, R. A. D.; Lin, C. S. K.; Vargas, C.; Luque, R. (Org. Biomol. Chem., 2014)

An Introduction to Organosulfur Chemistry - Cremlyn, R. J. (Wiley and Sons, 1996)

(untitled) - McReynolds, M. D.; Doughtery, J. M.; Hanson, P. R. (Chem. Rev., 2004)

(untitled) - Coran, A. Y. (J. Appl. Polym. Sci., 2003)

The Chemistry of the Functional Groups-The Chemistry of the Thiol Group - Patai, S. (Wiley, 1974)

March’s Advanced Organic Chemistry - Smith, M. B.; March, J. (Wiley, 2007)

Protective Groups in Organic Synthesis - Greene, T. W.; Wuts, P. G. M. (John Wiley & Son, 1999)

(untitled) - Sanz, R.; Martínez, A.; Miguel, D.; Álvarez-Gutiérrez, J. M.; Rodríguez, F. (Adv. Synth. Catal., 2006)

(untitled) - Zhang, X.; Rao, W.; Chan, P. W. H. (Synlett, 2008)

(untitled) - Haynes, R. K.; Katsifis, A. G.; Vonwiller, S. C.; Hambley, T. W. (J. Am. Chem. Soc., 1988)

(untitled) - Parker, K. A.; Johnson, W. S. (J. Am. Chem. Soc., 1974)

(untitled) - Sneen, R. A.; Kay, P. S. (J. Am. Chem. Soc., 1972)

(untitled) - Firouzabadi, H.; Iranpoor, N.; Jafarpour, M. (Tetrahedron Lett., 2006)

(untitled) - Han, X.; Wu, J. (Org. Lett., 2010)

(untitled) - Ouertani, M.; Collin, J.; Kagan, H. B. (Tetrahedron, 1985)

(untitled) - Inada, Y.; Nishibayashi, Y.; Hidai, M.; Uemura, S. (J. Am. Chem. Soc., 2002)

(untitled) - Corma, A.; Navas, J.; Ródenas, T.; Sabater, M. J. (Chem. – Eur. J., 2013)

(untitled) - Saxena, A.; Kumar, A.; Mozumdar, S. (Appl. Catal., A: Gen., 2007)

(untitled) - Bahrami, K.; Khodaei, M. M.; Khodadoustan, N. (Synlett, 2011)

(untitled) - Santoro, F.; Zaccheria, F.; Shaik, N. I.; Ravasio, N. (Top. Catal., 2012)

(untitled) - Zaccheria, F.; Psaro, R.; Ravasio, N. (Tetrahedron Lett., 2009)

(untitled) - Zaccheria, F.; Brini, S.; Psaro, R.; Scotti, N.; Ravasio, N. (ChemSusChem, 2009)

(untitled) - Zaccheria, F.; Mariani, M.; Psaro, R.; Bondioli, P.; Ravasio, N. (Appl. Catal., B, 2016)

(untitled) - Mariani, M.; Zaccheria, F.; Scotti, N.; Psaro, R.; Ravasio, N. (ChemistrySelect, 2016)

(untitled) - Huang, W.; Shen, Q.-S.; Wang, J.-L.; Zhou, X.-G. (Chin. J. Chem., 2008)

(untitled) - Baker, A.; Graz, M.; Saunders, R.; Evans, G. J. S.; Pitotti, I.; Wirth, T. (J. Flow Chem., 2015)

(untitled) - Guindon, Y.; Frenette, R.; Fortin, R.; Rokach, J. (J. Org. Chem., 1983)

(untitled) - Zhan, Z.-p.; Yu, J.-l.; Liu, H.-j.; Cui, Y.-y.; Yang, R.-f.; Yang, W.-z.; Li, J.-p. (J. Org. Chem., 2006)

(untitled) - Hikawa, H.; Toyomoto, M.; Kikkawa, S.; Azumaya, I. (Org. Biomol. Chem., 2015)